Does the Harvesting Technique Affect the Properties of Adipose‐Derived Stem Cells?—The Comparative Biological Characterization. Issue 5 (5th January 2017) - Bajek, Anna; Gurtowska, Natalia; Olkowska, Joanna; Maj, Małgorzata; Kaźmierski, Łukasz; Bodnar, Magdalena; Marszałek, Andrzej; Dębski, Robert; Drewa, Tomasz
ABSTRACT: The objective of this study was to evaluate complex biological properties of human stem cells isolated from adipose tissue (ASCs) harvested utilizing different methods: surgical resection (R), power‐assisted liposuction (PAL), and laser‐assisted liposuction (LAL). ASCs were isolated from healthy donors, due to surgical resection, power‐, and laser‐assisted liposuction. Isolated cells were characterized by their clonogenicity, proliferation rate, doubling time, multilineage differentiation, and senescence potential. The average number of ASCs from 1g/1 ml of solid adipose tissue/lipoaspirate was 2.9 × 10 5 ± 2.4 × 10 5, 1.1 × 10 5 ± 0.8 × 10 5, and 1.2 × 10 5 ± 0.7 × 10 5, respectively, for ASCsR, ASCsPAL, and ASCsLAL. However, number of colonies formed by ASCsR and ASCsPAL was significantly higher compared to the average number of colonies formed by ASCsLAL. Also, in comparison to other analyzed cell groups, ASCsPAL obtained the highest proliferative activity. All analyzed cells were characterized by stable expression of CD90 and CD44 markers during prolonged culture. Expression of CD34 and CD45 markers was decreasing in subsequent passages. Presented study shows that different ASCs collection method affects some basic characteristics of these cells, such as number of isolated cells, clonogeneity, or doubling time. J. Cell. Biochem. 118: 1097–1107, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Method of adipose tissue collection affects some characteristics of stem cells isolated from this tissue type. At the current state of knowledge, the best method of ASCs collection for medical purposes is power‐assisted liposuction.